Development of a Soil Temperature and Humidity Monitoring Device for Optimization of Chili Farming Using Arduino - Hannatul Mawe; Fitriani Fitriani (Bulletin of Network Engineer and Informatics, 2026)
The main problem often faced by chili farmers in the field is the difficulty in monitoring soil temperature and humidity conditions continuously, especially in large and remote areas. Environmental conditions that are not monitored accurately can cause a decrease in the quality and quantity of the harvest. This research aims to develop a soil temperature and humidity monitoring tool that is capable of providing real-time and accurate data to support the optimization of chili farming. This system is designed using an Arduino Uno microcontroller integrated with a DHT22 temperature sensor and a YL-69 soil moisture sensor. Measurement result information is displayed on the LCD screen and is also sent wirelessly using the SIM800L GSM module so that it can be accessed remotely. The method used is the prototype method, which includes the stages of needs identification, device design, prototype creation, functional testing and system evaluation. Data was obtained through literature studies, direct observations on agricultural land and interviews with farmers. The test results show that the tool can work stably, accurately and provide notifications of soil conditions that are appropriate to field conditions. This tool can assist farmers in making decisions regarding watering and maintaining chili plants. This monitoring system is expected to make agricultural processes more efficient, productive and based on real-time data.